If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 8) = 18 Reorder the terms: 3(8 + x) = 18 (8 * 3 + x * 3) = 18 (24 + 3x) = 18 Solving 24 + 3x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 3x = 18 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = 18 + -24 3x = 18 + -24 Combine like terms: 18 + -24 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 12-(2x+8)=x+16 | | 4x-6=3x | | 4(x-7)=40 | | 8x=5x+4.5 | | .66=3x | | -2x=-3x+8 | | 16p-4=4(2p-3) | | x+5=0 | | 32=12b-4 | | 2x-13=8x+27 | | 6y+5-y= | | 7x+12=-4x+78 | | 7+x=0.5(4x-2) | | 2y-4=-1-2y | | 3-4x=21x-47 | | 17+2x=31-5x | | 12X-10X-4=3 | | 12x-7=-3x+8 | | 7q+14=10q-55 | | x+2=3x-1 | | -10=-5x-35 | | -8x+7=4x-5 | | 7x-7=13+12x | | 12+8x=2x-6 | | 14m-10=3(4+m) | | 11n-6=60 | | 2(a-4)=4a-(2a-8) | | 7x-2-5X=18 | | (y-6)(y+2)= | | x^2+8x+6=0 | | 8w=16 | | 17x-7=8+14x |